Emir Abdelkader in the perspective of historians and writers of the French colonial school - rouabhi, Al-Ayashi (The Algerian Historical Journal, 2026)
Personality of Emir Abdelkader, his resistance and his biography drew the attention of many French historians, Some of them began to adopt positions hostile to him and his resistance, even to some of his stances in exile after the collapse of his resistance in the year 1847, and some of the pioneers of the Historical colonial school represented this group. This article attempts to present some of the most famous writings of this sect of historians, while at the same time trying to refute their allegations and highlight their intentions. This sect includes two principal groups: the writers and the French military historians.These had many military and administrative tasks during the 29th century.They wrote independent writings about Emir Abdelkader and his resistance,or they hinted at him when treating the history of Algeria at that time.However, the second sect involves the university teachers of history who prepared university theses and works, following the guidelines of the historical research and the rules of the scientific methodology.